Mengalisis Faktor-Faktor yang Mempengaruhi Ekonomi di Era Digital: Sebuah Studi Kasus di Kota Medan (2018-2023) - Lusia Oktaviani Br Tamba; Egi Ateta Barus; Maria Dwi Sianipar; Nadratul Aini Lubis; Viona lutfia Alfiaturahmah; Yogi Marselinus Turnip; Nina Novira (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The digital era has brought significant changes in human life, including in the economic field. The development of digital technology has influenced the way humans do business, transact and interact. The aim of this research is to determine the factors that influence economic growth in the digital era in the city of Medan in 2018-2023. The analysis techniques in this research are descriptive statistical analysis and multiple linear regression analysis. Based on the results of the discussion, it can be concluded that wholesale and retail trade, car and motorbike repairs greatly influence the movement of economic growth in Medan in the digital era, the policies implemented by the government are very important to maximize the positive impact of the digital economy on economic growth. Furthermore, the digital economy has the potential to encourage economic growth through increasing productivity, facilitating economic activities, and transforming business transactions from manual to automatic processes.